Mathematical model of malicious software spreading within computer networks - Семенов, Сергей Геннадиевич; Давыдов, Вячеслав Вадимович (Eastern-European Journal of Enterprise Technologies, 2013)
Previous researches indicate that the cases of malicious software infection and spread, which completely destroy computer systems, have become more frequent. Such software threats have proliferated recently but their damage ten times exceeds the damage caused by computer viruses which destroy data. Therefore, the development of mathematical model of the malicious software threats spreading with the possibility of complete computer systems destruction in order to localize them is a topical scientific task. In this article we propose a new mathematical model of malicious software spreading technology based on biological approach. It is based on PSIDR (Progressive Suspected-Infected-Detected-Recovered) model and named PSIDDR (Progressive Suspected-Infected-Detected-Destructed-Recovered). The analysis and comparative investigation of the developed model were processed and proved the expediency of its installation in stage of computer networks designing. Also the analysis and comparative investigation showed commensurability results of modeling with the known PSIDR model in low probability of malicious software attack with fatal consequences. Also the results showed a significant (more than 2 times) increase in accuracy of the simulation results in conditions of malicious software destructing ITCS (Informational Tele-Communication System) hardware components.